Ensuring the need is met: A 50‐year simulation study of the National Kidney Registry's family voucher program. Issue 3 (25th June 2020) - Cooper, Matthew; Leeser, David B.; Flechner, Stuart M.; Beaumont, Jennifer L.; Waterman, Amy D.; Shannon, Patrick W.; Ronin, Matthew; Hil, Garet; Veale, Jeffrey L.
Abstract : The National Kidney Registry (NKR) Advanced Donation Program enables living donors the opportunity to donate altruistically, or in advance of a potential recipient's transplant, and to receive a voucher that can be redeemed for a future transplant facilitated by the NKR. Family vouchers allow a donor to identify multiple individuals within their immediate family, with the first person in that group in need of a transplant being prioritized to receive a kidney. An increase in vouchers introduces concerns that demand for future voucher redemptions could exceed the supply of available donors and kidneys. A Monte Carlo simulation model was constructed to estimate the annual number of voucher redemptions relative to the number of kidneys available over a 50‐year time horizon under several projected scenarios for growth of the program. In all simulated scenarios, the number of available kidneys exceeded voucher redemptions every year. While not able to account for all real‐life scenarios, this simulation study found that the NKR should be able to satisfy the likely redemption of increasing numbers of vouchers under a range of possible scenarios over a 50‐year time horizon. This modeling exercise suggests that a donor family's future needs can be satisfied through the voucher program. Abstract : A data‐based Monte Carlo simulation model applied over a 50‐year horizon suggests that current practices would meet future needs for kidney redemptions through the Family Voucher Program. Englesbe and Pearson's editorial is on page 923 .